Analysis of The Influence of Timely Submission of Financial Statements of Transportation Companies Listed on The Indonesia Stock Exchange 2017-2021 - Rahmat Putra Ahmad Hasibuan, Nur Fadhilah Ahmad Hasibuan (Pusdikra Publishing, 2022)
The objective of the research was to find out and to analyze the influence profitability, leverage, liquidity, company size, auditor opinion and and KAP reputation partially on the timeliness of the submission of financial statements to transportation companies listed on the Indonesia Stock Exchange. The population in this study were 30 transportation companies listed in the Indonesia Stock Exchange in the period of 2017 - 2021. Samples were selected using saturated samples where all populations were included as samples. Data were processed using logistic regression test at a significance level of 5 percent using SPSS. The results of the study found empirical evidence that the variables of profitability, liquidity and auditor opinion affect the timeliness of the submission of financial statements. while the leverage variable, company size and KAP reputation do not have a significant effect on the timeliness of the submission of financial statements.